Association between health literacy and metabolic syndrome or healthy lifestyle characteristics among community-dwelling Japanese people. Issue 1 (December 2016) - Yokokawa, Hirohide; Fukuda, Hiroshi; Yuasa, Motoyuki; Sanada, Hironobu; Hisaoka, Teruhiko; Naito, Toshio
Abstract Background Few studies have assessed the association between health literacy (HL) and healthy lifestyle characteristics among Japanese people, and reports on the association between HL and prevalence of metabolic syndrome are also scarce. Methods The present cross-sectional study included 1817 (781 men and 1036 women) Japanese individuals who participated in a medical health checkup at Bange Kosei General Hospital and Takada Kosei Hospital in Fukushima, Japan, from April 2013–2014. Information regarding HL and healthy lifestyle characteristics listed in Breslow's seven health practices was collected by self-administered questionnaire. Results In multivariate logistic analysis, higher HL (≥14) was positively associated with healthy lifestyle characteristics [odds ratio (OR) = 2.08, 95 % confidence interval (CI) = 1.33–3.23] and inversely associated with prevalence of metabolic syndrome (OR = 0.67, 95 % CI = 0.48–0.95) among men. Among HL items, the ability to make decisions based on health-related information was significantly associated with healthy lifestyle characteristics (OR = 2.04, 95 % CI = 1.34–3.10 for men, OR = 1.38, 95 % CI = 1.30–1.85 for women) and inversely associated with prevalence of metabolic syndrome (OR = 0.62, 95 % CI = 0.44–0.88 for men, OR = 0.68, 95 % CI = 0.49–0.95 for women) in both sexes. Conclusions We found positive associations between HL and healthy lifestyle characteristics and an inverse association with prevalence of metabolic syndrome among men. Our findings also suggest that men and women are likely to engage in health-promoting behaviors and make decisions based on health-related information. These findings highlight the importance of comprehensive assessments, including HL, for health promotion in the community.